Succession of Insect-pests Infesting Sesame during Summer - Akbari, D. A.; Patel, R. M.; Sisodiya, D. B.; Mohapatra, A. R. (International Journal of Economic Plants, 2025)
Field experiment was carried out during summer (February–May, 2022) at Regional Research Station, Anand Agricultural University, Anand, Gujarat, India to find out the succession of insect pests and its fluctuation under the impact of biotic and abiotic factors on the abundance of major insect pests on sesame. Results revealed that the population of whitefly and jassid started from 10th standard meteorological week and till the 20th standard meteorological week. Population of Antigastra catalaunalis was first recorded during 12th standard meteorological week and reached at peak level during 15th standard meteorological week. Leaf, flower and capsule damage continuously increased and attained at peak during 16th and 20th standard meteorological week, respectively. The population of coccinellids and spider was highest during 14th and 15th standard meteorological week, respectively. The correlation with abiotic factors indicated that whitefly population showed highly significant negative correlation with wind speed and significantly negative correlation with minimum temperature, evening relative humidity and evening vapour pressure. Whereas, jassid population exhibited significantly negative correlation with WS, RH2 and VP2. However, A. catalaunalis showed significantly negative correlation with MinT, RH2 and VP2. Leaf damage showed significant negative correlation with RH2 and VP2. The flower damage had highly significant correlation with VP2 and significant negative correlation were observed with MinT and RH2. While, capsule damage had significantly positive correlation with MinT and VP2. Whereas, the natural enemies viz., coccinellids and spider exhibited significantly negative correlation with RH2.